Programa psicoeducativo para potenciar las habilidades sociales en los niños y niñas del quinto año de educación básica de la escuela Jóse Ingenieros Nro. 2, periodo 2014-2015 - Cumbicos Salinas, Magali Janeth (2016)
For this research the objective was formulated Implement a psychoeducational program to enhance the social skills of children, a descriptive, cross-sectional, quasi-experimental design was used. Methods used: scientific, deductive, inductive, analytical - synthetic, logical, descriptive and statistical. Messy scale for the students was applied and a questionnaire of social interaction skills, worked with a sample of 20 students in 4 girls and 16 boys. Results: discrepados by applying the pre-test, found that 35% have difficulties skills to make friends, 25% indicate problems in conversational skills and 25% indicate difficulties related to emotions skills and feelings 30% have obstacles in problem solving skills. Clearly, by applying the psychoeducational program was an improvement in the development of social skills corroborating with the implementation of the post-test was achieved show that 80% of skills to men and women improved, 70% of Conversational skills up 65% of skills related to emotions and feelings increased to 60% from solving skills increased interpersonal problems. The psychoeducational program reached a low positive correlation (x, y). It is concluded that in the population studied overprotection brings loss of freedom that affects the development of social, cognitive and emotional skills that negatively influence the psychological state of the sample